From Saints to Mere Mortals: The Desacralization of Disappeared Persons in the Work of Félix Bruzzone and Mariana Eva Pérez - Ostrom, Timothy J. (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2024)
This article explores a recent development in Argentine post-dictatorship literature: the desacralization of disappeared persons. The narrative of Félix Bruzzone and Mariana Eva Pérez marks a substantial break with the production of the genre from the end of the dictatorship to the early 2000s, which is characterized by the sacralization of the disappeared within a highly idealized and sentimental rendering of the political militancy of the 1970s. Through a playful poetics of irreverence, transgression and profanation, Bruzzone and Pérez forge new modes of representing dictatorship at a moment when memory discourse was being appropriated by both the State and mass media.